On Interruption: Working through the past and the arts. (4th July 2021) - Kobialka, Michal
Abstract : The events of 2020 are a central metaphor for the interruption and the possibility of putting a halt to that which is. They make us think of a 'world without us', or demand a social action that would make us 'think otherwise'. This essay investigates what conditions need to be fulfilled for this vision to be sustainable, rather than a momentary intensification and radicalization of statements, which, as evidenced by the aftermath of those other interruptions in 1968 or 1989, can rapidly exhaust emancipatory endeavours. With this dose of historiographic scepticism, I begin this essay about Walter Benjamin's, Theodor Adorno's and Tadeusz Kantor's encounters with their own historical interruptions, registered in their critiques of the relationship between historical conditions and aesthetic theory or practice. Even though their critiques come from very different contexts and historical moments (Benjamin 1934; Adorno 1936, 1962, 1968; Kantor 1949), can their criticism, under the name of refractory art in both senses of the word—as a negation and a deviation from the route that proceeded it—be of use to us today while we are working through our pasts as well as the relationship between historical events and art in this present?